Directions activation state support of enterprises grainproduct subcomplex of agriculture: the economic aspect - Nadiya Kulchytska; Yuriy Buhel (Cхід, 2013)
The article discusses the basic problems of state support agriculture. Particular attention is paid to the problems of government subsidies and their effective use, the integration of agriculture and increase agricultural investment attractiveness for foreign investors.